ANALISIS FUNDAMENTAL DAN NILAI INTRINSIK SAHAM DENGAN METODE FREE CASH FLOW TO EQUITY DAN RELATIVE VALUATION UNTUK PENGAMBILAN KEPUTUSAN INVESTASI (STUDI KASUS PT KALBE FARMA TBK) - Tio, Erika (Jurnal Manajemen Update, 2021)
The purpose of this study is to find the intrinsic value of KLBF shares by identifying the company's external and internal factors and then continuing with the stock valuation process. The valuation method used is Free Cash Flow To Equity (FCFE) and relative valuation with the Price Earning Ratio (PER) approach. The results of the valuation of KLBF shares using the FCFE method obtained KLBF's intrinsic value of Rp 1005,-/share, while the market price of KLBF shares as of April 30, 2021 was Rp 1440,-/share. Thus, KLBF's share price was overvalued. Based on the valuation using the relative valuation method, the PER KLBF is 24.95 times, while the industry average PER is 20.09 times. Based on the results, the recommendation given is to sell or not buy KLBF shares, and if you want to buy KLBF shares you can wait when the price is undervalued.Keywords: fundamental analysis, intrinsik value, FCFE, relative valuationDAFTAR PUSTAKAAdam, Fahmi. (2020). Stock Valuation and Business Performance of PT Ultrajaya Milk Industry, Tbk, Institut Teknologi Bandung, Indonesia.Arikunto, Suharsimi. (2010). Prosedur Penelitian Suatu pendekatan Praktek. Jakarta: Rineka Cipta. Asnawi, Said Kelana dan Wijaya, Chandra. (2006). Metodologi Penelitian Keuangan: Prosedur, Ide, dan Kontrol. Edisi Pertama.Yogyakarta: Graha Ilmu.Badan Pusat Statistik. (2020). Pertumbuhan Ekonomi Indonesia Triwulan III-2020. Berita Resmi Statistik No. 85/11/Th. XXIII.Bodie, Kane, Marcus. (2014). Manajemen Portofolio dan Investasi, Edisi 9-Buku 2. Jakarta: Salemba Empat. Boediono.  (2014). Ekonomi Internasional - Pengantar Ilmu Ekonomi No. 3. Yogyakarta: BPFE UGM. Brigham & Houston. (2018). Dasar-Dasar Manajemen Keuangan. Jakarta: Salemba Empat.Brilliand, D.P., Hidayat, R.R., & Darmawan, A. (2014).  Analisis Fundamental dalam Penilaian Harga Saham dengan Menggunakan Metode Dividend Discounted Model dan Price Earning Ratio (Studi pada Perusahaan Multinasional Sub Sektor Semen yang terdaftar di Bursa Efek Indonesia Periode 2013-2015). Jurnal Administrasi Bisnis, 37 (2).Budiman, R. & Darmawan, A. (2010). Analisis Fundamental Harga Saham Perusahaan dengan Menggunakan Metode Discounted Cash Flow dan Price Earning Ratio (Studi pada Perusahaan Multinasional yang Menjadi Anggota Indeks Sektor Properti di BEI Periode 2012-2016). Jurnal Administrasi Bisnis, 63 (1).Chartered Global Management Accountant. (2013, 11 Juni). Porter’s Five Forces of Competition Position Analysis. Diakses pada 5 November 2020, dari https://www.cgma.org/resources/tools/essential-tools/porters-five-forces.html.Damodaran, Aswath. (2002). Investment Valuation: Tools and Techniques for. Determining the Value of Any Asset. New York: John Wiley & Sons,. Inc.Darmadji, Tjiptono dan Fakhruddin. (2012). Pasar Modal di Indonesia. Jakarta: Salemba Empat.Fahmi, Irham. (2012). Pengantar PasarModal. Bandung: Alfabeta.Ferdinand, Augusty. (2014). Metode Penelitian Manajemen. Semarang: BP Universitas Diponegoro.Graham, Benjamin. (1949). The Intelligent Investor. Buffalo, Ny: Harper.Gusni. (2014). The Applications of Discount Cash Flow, Abnormal Earning, and Relative Valuation Approach, Universitas Widyatama, Indonesia.Hadi, Nor. (2013). Pasar Modal. Yogyakarta: Graha Ilmu.Hanafi, Mamduh M., dan Halim, Abdul. (2016). Analisis Laporan Keuangan Edisi ke-5. Yogyakarta: UPP STIM YKPN.Handadari, Asasih Sophia. (2012). Valuasi Nilai Intrinsik Saham PT Kalbe Farma Tbk (KLBF), Universitas Gadjah Mada, Indonesia.Haritha, M., Ravi, V, & Ravisankar, O. (2013). Intrinsic Value A Base to Pick Scrip. Journal of Business and Management, 15 (3).Hartono, Hartono. (2017). Teori Portofolio dan Analisis Investasi. Edisi 11. Yogyakarta: BPFE Yogyakarta. Husnan, Suad. (2015). Dasar-Dasar Teori Portofolio & Analisis Sekuritas. Edisi 5. Yogyakarta: UPP STIM YKPN.Kasmir. (2012). Analisis Laporan Keuangan. Jakarta : PT. Raja Grafindo Persada.Kasmir. (2016). Analisis Laporan Keuangan. Jakarta: PT. Raja Grafindo Persada.Kementerian Perindustrian. (2020). Analisis Perkembangan Industri Indonesia Edisi I-2020. Pusdatin Kemenperin.KPPU. (2019). Ringkasan Eksekutif Penelitian Sektor Strategis Terkait Pencegahan Praktek Monopoli dan Persaingan Usaha Tidak Sehat pada Industri Farmasi di Indonesia. Direktorat Ekonomi Kedeputian Kajian dan Advokasi KPPU.Kalbe Farma. (2015). Laporan Tahunan 2015. Jakarta: Kalbe Farma.Kalbe Farma. (2016). Laporan Tahunan 2016. Jakarta: Kalbe Farma.Kalbe Farma. (2017). Laporan Tahunan 2017. Jakarta: Kalbe Farma.Kalbe Farma. (2018). Laporan Tahunan 2018. Jakarta: Kalbe Farma.Kalbe Farma. (2019). Laporan Tahunan 2019. Jakarta: Kalbe Farma.Kalbe Farma. (2020). Laporan Tahunan 2020. Jakarta: Kalbe Farma.Mankiw N,Gregory. (2009). Macroeconomics, 7th Edition. New York: Worth Publishers.Miles, D., Scott, A. (2005). Macroeconomics: Understanding the Wealth of Nations (2nd ed). England: John Wiley & Sons, Ltd.Mubarok, Fithrul. (2019). Top 10 Perusahaan Farmasi Terbesar Indonesia Terbaru. Diakses pada 10 Maret 2021. https://farmasiindustri.com/industri/top-10-perusahaan-farmasi-indonesia.html/amp.Natalia, Dea. (2019). Analisis Valuasi Saham Menggunakan Pendekatan Dividend Discounted Model (DDM), Price Earning Ratio (PER), dan Price to Book Value (PBV) untuk Pengambilan Keputusan Investasi (Studi Empiris pada Perusahaan Sektor Barang Konsumsi yang Listed di Bursa Efek Indonesia tahun 2013-2017), Universitas Sanata Dharma, Indonesia.Ningtiyas, Eka Riski. (2012). Penggunaan Metode Free Cash Flow to Equity dan Relative Valuation dalam Penilaian Saham PT Bank Rakyat Indonesia Tbk, Universitas Indonesia, Indonesia.Nopirin. (2013). Pengantar Ilmu Ekonomi Makro & Mikro. Yogyakarta: BPFE.Rahardja, Prathama dan Manurung, Mandala. (2008). Teori Ekonomi Makro. Jakarta: LPFEUI.Rahmawantari, Dhistianti Mei dan Puspitaningtyas, Ayu. (2019). P/E Ratio dalam Valuasi Saham untuk Pengambilan Keputusan Investasi. Jurnal Ekonomi dan Industri, 20 (2).Samsul, Muhamad. (2006). Pasar Modal Dan Manajemen Portofolio. Surabaya: Erlangga.Sartono, Agus. (2010). Manajemen Keuangan Teori dan Aplikasi. Edisi. Keempat. Yogyakarta: BPFE. Saryono. (2010). Metode Penelitian Kualitatif. Bandung: Alfabeta.Subandi. (2011). Ekonomi Pembangunan. Bandung: Alfabeta.Sugiyono. (2012). Metode Penelitian Kuantitatif Kualitatif dan R&D. Bandung: Alfabeta.Sukirno, Sadono. (2012). Makro Ekonomi Modern. Jakarta: PT. Raja Grafindo Perkasa.Sukmadinata, Nana Syaodih. (2010). Metode Penelitian Pendidikan. Bandung: PT Remaja Rosdakarya.Tambunan, Andy. (2007). Menilai Harga Wajar Saham. Cetakan Kedua. PT Grasindo, Jakarta.Tandelilin, Eduardus. (2010). Portofolio dan Investasi Teori dan Aplikasi. Edisi pertama. Yogyakarta: Kanisius.Tandelilin, Eduardus. (2017). Pasar Modal: Manajemen Portofolio dan Investasi. Yogyakarta: Kanisius.Weston, J. Fred dan Copeland, Thomas E. (2001). Manajemen Keuangan Jilid I. Edisi ke-9. Jakarta : Binarupa Aksara.Winata, Mas Zuchrizal Rasyidian. (2020). Valuasi Saham PT Industri Jamu dan Farmasi Sido Muncul, Institut Teknologi Bandung, Indonesia.Wisudana, Priatama. (2011). Penilaian Harga Wajar Saham Menggunakan Model Discounted Cash Flow dan Relative Valuation (Studi Kasus PT Bukit Asam Tbk dan PT Adaro Tbk Periode 2005-2010), Universitas Indonesia, Indonesia.Yovinna, Erlyn. (2011). Analisis Penilaian Harga Wajar Saham dengan Metode Discounted Cash Flow (Studi Kasus pada PT Kalbe Farma Tbk), Sekolah Tinggi Ilmu Ekonomi Indonesia Banking School, Indonesia.